(untitled) (Journal of the College of Basic Education, 2022)
What distinguishes the theater is being accepted all the readings، and adapts to all fields of knowledge، and the evidence that all monetary approaches that we received through acculturation find Zaltha in theatrical discourse، as a heavy material does not skimp on any critic or a monetary approach to meet the saturation of knowledge. In this regard، we suggest one of the most communicative theories that worked on the public discourse and the discourse theatrical especially made context of the first concerns، it comes to functional Ballsaniyat in splitting deliberative، Valtdaulyat can be codified theatrical discourse، and make signs of the tree are specific and accurate interpretations، and then the subject of theatrical discourse becomes clear، read its meaning will be standardized among all recipients، the data can be extracted through the functions of language and levels، and base the dialogue، in addition to the rhythm of verbal language، which seems by supply emphasis multiplier word that pronounced actor on stage doing، because they do do it now، in the characters you receive that، you hear، as directed Alleha.altkoan double for the theater، text / display makes it an open offer and described as Annie and transient، it does not repeat twice that during the narration produces a system of allied relations with the linguistic relations problem for dialogue give speeches characters conditions Allfezah imaginary Faiser difficult then to imagine a presentation without text even in the absence of spoken words.